Analyzing Methodology of Increasing Students' Competence Using Pentesting Platforms on The Subject of Information Security - Ibragimov U.M.; Ahadov A.M. (Global Scientific Publishing, 2022)
The scientific research illustrates that using penetration testing for teaching students Information Security Science and it has analyzed of measuring the vulnerability to data compromises provides the scientific background and analytic techniques to understand and measure the risk associated with information security threats. Penetration tester usually begins by gathering as much information about the target as possible. Then he identifies the possible vulnerabilities in the system by scanning.
Keywords: Computation; penetration testing; multiple phases; test case